Financial Literacy and Investment Socialization for Generation Z - Pradana, Haris Kondang; Febriansyah, Febriansyah; Husairi, Ridwan; Pilisia, Ade Elfhina (Zabags International Journal of Engagement, 2024)
This socialization is carried out to help the internet generation or generation Z people who should have knowledge about financial literacy and investment. So that you are able to make good and appropriate financial decisions. This Community Service activity aims to socialize financial and investment literacy to Generation Z in the West Muara Sabak area. The activity was carried out using the socialization method, then continued with discussion and question and answer as well as filling out a questionnaire. The activity participants were students in the Muara Sabak Barat area, East Tanjung Jabung, totaling 30 participants. Based on the results of the questionnaire, it is known that there are still many students who do not know or find out about financial literacy and investment. Overall, this socialization has increased participants' knowledge of managing their finances.